REDUCING CRIME THROUGH THE THEATRE: AN ANALYSIS OF FOLUKE OGUNLEYE’S JABULILE - Akaenyi, Nkiruka Jacinta (International Review of Humanities Studies, 2021)
This study examines the connection between family conditions and the criminal behaviours of children. Over the years, drama has been used to address the socio-political, economic and security challenges in different societies. The goal of these dramatists is to chart the way forward for a harmonious political, economic and social system. It is in this wise that, Foluke Ogunleye used her knowledge of drama to address serious issues affecting the progress and stability of the nation. This study finds that the explosion of crime in the nation is linked to the fragile family system surrounding the children’s upbringing by their respective families. This paper analyzes one of Foluke Ogunleye’s plays, Jabulile in an attempt to educate Nigerian families on what is expected of them as far as the issue of national security is concerned. This is done with the recognition that the family is the first unit of socialization. This study recommends that proper socialization of children by their parents is therefore a stepping stone for a harmonious socio-political system.